DIMENSI EKONOMI REGIONAL DAN PEMBANGUNAN KOTA (STUDI KASUS: KOTA BANDA ACEH) - Dewi Wahyuna; Weri Weri (Fakultas Ekonomi dan Bisnis UNSYIAH, 2020)
AbstractThis study aims to analyze the influence of regional economic dimensions on development inKota Banda Aceh. The data used are secondary data sourced from the Central Statistics Agency(BPS). The data analysis tool used in this study is multiple linear regression. The results showedthat housing and settlement basic infrastructure, education, internet access, health and regionalminimum wages had a positive and significant impact on the development in Kota Banda Aceh.Thus, to improve and equality development, the government of Kota Banda Aceh need to providethe housing and settlement basic infrastructure, education, internet access, health and regionalminimum wages.Keywords: Dimension, Regional, Internet, and Regional Minimum Wages